Early-Stage IM Treatment with the Host-Derived Immunostimulant CPDI-02 Increases Curative Protection of Healthy Outbred Mice Against Subcutaneous Infection with Community-Acquired Methicillin-Resistant Staphylococcus aureus USA300 - Jason P. Stewart; Caleb M. Sandall; Jacob E. Parriott; Stephen M. Curran; Russell J. McCulloh; Donald R. Ronning; Joy A. Phillips; Robin Schroeder; Christy Neel; Kelly F. Lechtenberg; Samuel M. Cohen; Yazen Alnouti; et al. (Pharmaceutics)
Background/Objectives: Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) greatly complicates the treatment of skin and soft tissue infections (SSTI). It was previously found that subcutaneous (SQ) treatment with the mononuclear phagocyte (MP)-selective activator complements peptide-derived immunostimulant-02 (CPDI-02; formerly EP67) and increases prophylaxis of outbred CD-1 mice against SQ infection with CA-MRSA. Here, we determined if treatment with CPDI-02 also increases curative protection. Methods: Female CD-1 mice were challenged SQ with CA-MRSA USA300 LAC, then CPDI-02 or inactive scCPDI-02 was administered by a topical, SQ, IM, or IV route at 6 or 24 h post-challenge. Abscess sizes were compared over 10 days and CA-MRSA burden, neutrophils, MP, and pro-inflammatory cytokines were compared in subcutaneous abscesses. CPDI-02 PK and distribution in female CD-1 mice were compared after IM or IV dosing and CPDI-02 toxicity in male and female CD-1 mice was determined by IM dose escalation and repeat IM dosing. Results: Repeat IM treatment starting at 6 h post-challenge decreased maximum abscess surface area, CA-MRSA burden, and time to resolution, whereas repeat treatment by a topical, SQ, or IV route had no effect. Repeat treatment starting at 24 h post-challenge was ineffective by the current routes. Single IM treatment starting at 6 h post-challenge was as effective as repeat IM treatment, increased systemic exposure to CPDI-02, and, in subcutaneous abscesses, initially decreased IL-1β and increased MP. CPDI-02 was tolerated between 130 and 170 mg/kg after IM dose escalation and between 65 and 130 mg/kg after repeat IM dosing with males being more tolerant. Conclusions: Single early-stage IM treatment with CPDI-02 may increase curative protection against SSTI caused by CA-MRSA and/or other pathogens controlled by activated MP.